2004
DOI: 10.1017/s0790966700008417
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of antipsychotic drugs from adults with intellectual disabilities

Abstract: Objectives: There is a view that antipsychotic drugs can be successfully withdrawn from people with intellectual disabilities with resultant health gain. This study critically examines whether antipsychotic drug withdrawal is beneficial.Methods: 119 adults with intellectual disabilities were included in a programme of antipsychotic drug withdrawal.Results: The clinical outcomes of this programme are poor. Only 7.6% completely withdrew from antipsychotic drugs, and 48.7% experienced onset/deterioration in probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…However, studies in which antipsychotics have been withdrawn from these patients have reported that a significant proportion deteriorate in their behaviour (Branford 1996; Ahmed et al. 2000; Stevenson et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies in which antipsychotics have been withdrawn from these patients have reported that a significant proportion deteriorate in their behaviour (Branford 1996; Ahmed et al. 2000; Stevenson et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the effectiveness of antipsychotics for problem behaviour in patients with ID found no definite evidence for efficacy, while recognising this is an underresearched area (Brylewski & Duggan 1999). However, studies in which antipsychotics have been withdrawn from these patients have reported that a significant proportion deteriorate in their behaviour (Branford 1996;Ahmed et al 2000;Stevenson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Stevenson and colleagues, writing in the aftermath of the restrictions imposed on the use of the first-generation agent thioridazine in 2000, contested that wide-scale antipsychotic withdrawal in this group is likely to cause serious harm, including precipitating increases in behaviour problems and mental ill-health. 60 Overall results from studies that report behavioural outcomes are inconclusive. Both deKuijper et al 47 and Ahmed et al 32 report no change, or even improvement in behaviour after antipsychotic discontinuation, although those whose behaviour deteriorated did not complete the withdrawal programme.…”
Section: Predictors Of Successful Antipsychotic Reduction or Discontimentioning
confidence: 99%
“…Studies with no individual outcomes reported, including those reporting average changes in medication use only Findholt and Emmett 81 Luchins et al 59 Bisconer et al 82 Branford 57 Howerton et al 83 Ruggerini et al 84 Lim 85 Observational studies with no active intervention to reduce or discontinue antipsychotic drugs Wressell et al 86 Etherington et al 87 Gravestock 88 Branford 89 Studies reporting no new suitable information Branford 90 Studies where most or all participants were taking antipsychotic for mental illness Pary et al 91 Sovner 92 Davies et al 93 Margetić and Aukst-Margetić 94 Stonecipler et al 95 Janowsky et al 96 Studies describing switch of antipsychotics Matthews and Weston 58 Stevenson et al 60…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Significant minorities experienced onset or deterioration of adverse effects with the introduction of new drugs or of challenging behaviour or mental ill health, and costs to the specialist psychiatric service rose. 38 However, a randomised controlled withdrawal study reported more positive results. Ahmed et al 39 conducted a trial in which 56 participants were randomised to an experimental group (n = 36) or a control group (n = 20).…”
Section: Withdrawal Of Antipsychotic Medicationmentioning
confidence: 99%